Implementasi Metode Problem Solving dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam di SMA Negeri 3 Purwakarta: Studi Eksperimental pada Kelas X - Wishal, Wishal Luthfikha; Tabroni, Imam; Saleh, Abdurahman (Ahdāf: Jurnal Pendidikan Agama Islam, 2024)
This research was conducted to investigate the effectiveness of teaching methods in enhancing the learning outcomes of Islamic Religious Education (PAI) for 10th-grade students at Sekolah Menengah Atas Negeri 3 (SMAN 3) Purwakarta. This study aimed to compare the learning outcomes of students between the lecture method and the Problem-Solving method. The research method employed was an experiment involving two groups of students, namely the experimental group taught using the Problem-Solving method and the control group taught using the lecture method. Learning outcome data was collected through pre-tests and post-tests and analyzed using the Independent T-Test statistical analysis. The research results indicated that the Problem-Solving method significantly improved students' learning outcomes (mean=65.51) compared to the lecture method (mean=41.67). The average percentage of students' learning outcomes using the Problem-Solving method reached 81.89%, categorized as "Good," while the lecture method only reached 52.08%, categorized as "Less Good." Based on these findings, it is recommended that teachers consider the use of the Problem-Solving method in PAI learning to enhance students' learning outcomes. The integration of this method can bring significant benefits, such as improving critical thinking, student engagement, and overall learning outcomes. Therefore, this research provides a crucial contribution to the development of more effective teaching strategies in the field of religious education.